Ventilatory effects of substance P-saporin lesions in the nucleus tractus solitarii of chronically hypoxic rats - Wilkinson, Katherine A. (American Physiological Society, 2011)
During ventilatory acclimatization to hypoxia (VAH), time-dependent increases in ventilation lower Pco(2) levels, and this persists on return to normoxia. We hypothesized that plasticity in the caudal nucleus tractus solitarii (NTS) contributes to VAH, as the NTS receives the first synapse from the carotid body chemoreceptor afferents and also contains CO(2)-sensitive neurons. We lesioned cells in the caudal NTS containing the neurokinin-1 receptor by microinjecting the neurotoxin saporin conjugated to substance P and measured ventilatory responses in awake, unrestrained rats 18 days later. Lesions did not affect hypoxic or hypercapnic ventilatory responses in normoxic control rats, in contrast to published reports for similar lesions in other central chemosensitive areas. Also, lesions did not affect the hypercapnic ventilatory response in chronically hypoxic rats (inspired Po(2) = 90 Torr for 7 days). These results suggest functional differences between central chemoreceptor sites. However, lesions significantly increased ventilation in normoxia or acute hypoxia in chronically hypoxic rats. Hence, chronic hypoxia increases an inhibitory effect of neurokinin-1 receptor neurons in the NTS on ventilatory drive, indicating that these neurons contribute to plasticity during chronic hypoxia, although such plasticity does not explain VAH.